La colección Iconográfica del compositor Joaquín Turina: Descripción y análisis documental - Olivera Zaldua, María (Cuadernos de Documentación Multimedia, 2009)
The iconographic archives of composer Joaquín Turina form a part of his artistic legacy. These archives are made up of approximately 6,000 original documents, which have been conserved by his heirs. The composer reveals his personality and his lifestyle in this collection, both through the postcards he collected and sent to his family from his travels, as well through his personal photographs and those which he purchased or gave away as gifts. The purpose of this study is to describe and analyze in depth all of this material.
Keywords: Documentary analysis; Iconographic collection; Photographic documentation; Photography; Iconography; Joaquín Turina; Postcard